Phospholipase A2 Receptor Autoantibodies as a Novel Serological Biomarker for Autoimmune Thyroid Disease Associated Nephropathy - Huang, Biao; Zhang, Yi; Wang, Liang; Wu, Qingqing; Li, Ting; Zhang, Jue; Zhang, Qiuhua; Sheng, Huiming; Bao, Jiandong; Hu, Zhigang (Frontiers in Immunology, 2020)
AIMS To develop a highly sensitive immunoassay for PLA2R autoantibodies and study the relationship between PLA2R autoantibodies and autoimmune thyroid disease-associated nephropathy. METHODS We applied a highly sensitive time-resolved fluoroimmunoassay to quantitatively detect the concentration of phospholipase A2 receptor (PLA2R) antibodies in the serum of patients with Graves’ disease, Hashimoto’s thyroiditis (HT), nephrotic patients with idiopathic membranous nephropathy (IMN), and normal controls. We immunohistochemically analyzed the existing PLA2R target antigen in the thyroid tissue of patients with Graves’ disease and HT, as well as the nephridial tissue of nephrotic patients with IMN. RESULTS PLA2R antibody concentrations in the serum of normal controls, patients with nodular goiter, Graves’ disease, and HT, as well as patients with IMN were 1.13 ± 0.43, 1.07 ± 0.22, 2.12 ± 2.11, 8.07 ± 4.74, and 15.91 ± 19.50 mg/L, respectively. PLA2R antibody concentration in the serum and the area under the receiver operating characteristic curve in patients with HT and IMN were increased significantly. Immunohistochemistry revealed obvious staining of PLA2R in tissues from patients with HT, with a positive rate of 66.67%. CONCLUSIONS PLA2R is a potential pathogenic target antigen for HT, and the production of PLA2R antibodies may cause autoimmune thyroid disease-associated nephropathy.